Your Everyday, Average Academic - Melanie E. Ward (Institute for the Study of Labor (IZA), 1999)
The data described in this paper come from a unique cross section study collected by the author, using a postal questionnaire, of five Scottish Universities: Aberdeen, Dundee, Glasgow, Heriot-Watt and St. Andrews undertaken in 1995/6. It encompasses detailed information on the personal and working history of 900 academics. The paper aims to provide the reader with a fuller picture of the characteristics of today?s average UK academic. Second, it aims to take advantage of this more detailed information to make some comment on the current debate in the UK concerning gender discrimination and underpayment in academia.
Keywords: J44; 330; Academic profession; underpayment; gender; publication; average characteristics; Hochschullehrer; Wissenschaftler; Besoldung; Erwerbsverlauf; Arbeitsmarktdiskriminierung; Großbritannien; Schottland